Dynamic myelin regulation as a novel form of neural plasticity - . Yuliana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Dynamic changes in myelin could optimize information transmission in neuralcircuits and enhance conduction velocity. This review aimed to provide anunderstanding of how dynamic myelin plasticity is important in neuronalactivity and how astrocytes have an important role that is not equal in theperipheral nervous system. Myelin is dynamically regulated by neuronalactivity. It takes part continuously in nervous system plasticity duringdevelopment. Newly differentiating oligodendrocytes can create a new myelinsheath. Mature myelin sheaths can grow again in adults. Oligodendrocytesinteract with astrocytes in the central nervous system through gap junctions.Astrocytes have an important role as synaptic network integrators; therefore,decreasing astrocyte numbers will cause a loss of presynaptic plasticity. Theconcept considers plasticity as a mechanism that depends on myelination.Higher brain functions and myelination interplay in the hippocampus andprefrontal cortex. The mechanism and function of these changes remainpoorly understood. Genetic, neural activity, environment, and axonal activitymight play important roles. Dynamic myelin regulation reveals a new form ofneural plasticity. Myelination is similar to synapse formation and plasticity. Itenables plasticity in the central nervous system and helps improve the learningprocess.